Multi-functional flow cytometry analysis of CD4+ T cells as an immune biomarker for latent tuberculosis status in patients treated with tumour necrosis factor (TNF) antagonists. (24th April 2014) - Sauzullo, I; Scrivo, R; Mengoni, F; Ermocida, A; Coppola, M; Valesini, G; Vullo, V; Mastroianni, C M
Summary: Although monitoring tuberculosis (TB) infection during long-term treatment with tumour necrosis factor (TNF) antagonists is of great importance, no monitoring strategy has yet proved successful. Indeed, even the newly proposed interferon-gamma release assays (IGRAs) are known to produce dynamic changes in IFN-γ plasma levels, making them unreliable indicators of patients' pathological/clinical status. We used intracellular cytokine flow cytometry (ICCFC) to investigate the performance of multi-functional CD4 + T cells producing IFN-γ, interleukin (IL)-2 and/or TNF in response to Mycobacterium tuberculosis -specific antigens in subjects treated with TNF antagonists. Patients were classified into three groups based on their TB status before commencement of treatment and on IFN-γ level fluctuations evaluated by IGRA during a 36-month follow-up period. The cytokine profile of M. tuberculosis -specific CD4 + T cells showed that latent tuberculosis infection (LTBI) subjects had a higher frequency of double-positive IFN-γ + IL-2 + CD4 + T cells and triple-positive IFN-γ + IL-2 + TNF + CD4 + T cells compared to those without LTBI, who showed IFN-γ-level fluctuations over time. In contrast, this latter group of patients showed similar proportions of cells producing IFN-γ alone, IL-2 alone and IL-2 in combination with TNF in response to M. tuberculosis -specific antigens. It therefore appears that patients with and without LTBI infection are characterized by different intracellular cytokine profiles. This is the first study evaluating ICCFC in patients treated with TNF antagonists, and suggests that multi-functional analysis of CD4 + T cells could be useful for ruling out TB infection in patients classified at screening as LTBI-negative but who show IGRA fluctuations under long-term TNF antagonist treatment.